Transversity 2005 : Como, Italy, 7-10 September 2005 - Barone, Vincenzo, 1964-; Ratcliffe, Philip G. (World Scientific Pub., 2006)
The notion of transversity in hadronic physics has been with us for over 25 years. Intriguing though it might have been, for much of that time transversity remained an intangible and remote object, of interest principally to a few theoreticians. In recent years, transversity and transverse-spin effects in general have grown as both theoretical and experimental areas of active research. This increasing attention has now matured into a thriving field with a driving force of its own. The ever-growing bulk of data on asymmetries in collisions involving transversely polarised hadrons demands a more solid and coherent theoretical basis for its description. Indeed, it now appears rather clear that transversity and other closely related properties play a significant role in such phenomena. As part of a Ministry-funded inter-university Research Project, this workshop was organised to gather together experimentalists and theoreticians engaged in investigating the nature of transverse spin in hadronic physics, with the intent of favouring the exchange of up-to-date theoretical and experimental ideas and news on the subject. Over 70 physicists took part and very nearly all the major experiments involved in transverse-spin studies were officially represented, as too were the main theory groups working in the field. New results and new analyses sparked many interesting and lively discussions.